Grief A Philosophical Guide - Cholbi, Michael (Princeton University Press, 2022)
An engaging and illuminating exploration of grief-and why, despite its intense pain, it can also help us growExperiencing grief at the death of a person we love or who matters to us-as universal as it is painful-is central to the human condition. Surprisingly, however, philosophers have rarely examined grief in any depth. In Grief, Michael Cholbi presents a groundbreaking philosophical exploration of this complex emotional event, offering valuable new insights about what grief is, whom we grieve, and how grief can ultimately lead us to a richer self-understanding and a fuller realization of our humanity.Drawing on psychology, social science, and literature as well as philosophy, Cholbi explains that we grieve for the loss of those in whom our identities are invested, including people we cherish without personally knowing, such as public figures. Their deaths not only deprive us of worthwhile experiences; they also disrupt our commitments and values. Yet grief is something we should embrace rather than avoid, an important part of a good and meaningful life. The key to understanding this paradox, Cholbi says, is that grief offers us a unique and powerful opportunity to grow in self-knowledge by fashioning a new identity. Although grief can be tumultuous and disorienting, it also reflects our distinctly human capacity to rationally adapt as the relationships we depend on evolve.An original account of how grieving works and why it is so important, Grief shows how the pain of this experience gives us a chance to deepen our relationships with others and ourselves